Granulocyte colony-stimulating factor exacerbates hematopoietic stem cell injury after irradiation. Issue 1 (December 2015) - Li, Chengcheng; Lu, Lu; Zhang, Junling; Huang, Song; Xing, Yonghua; Zhao, Mingfeng; Zhou, Daohong; Li, Deguan; Meng, Aimin
Abstract Background Exposure to a moderate to high dose of ionizing radiation (IR) not only causes acute radiation syndrome but also induces long-term (LT) bone marrow (BM) injury. The latter effect of IR is primarily attributed to the induction of hematopoietic stem cell (HSC) senescence. Granulocyte colony-stimulating factor (G-CSF) is the only treatment recommended to be given to radiation victims soon after IR. However, clinical studies have shown that G-CSF used to treat the leukopenia induced by radiotherapy or chemotherapy in patients can cause sustained low white blood cell counts in peripheral blood. It has been suggested that this adverse effect is caused by HSC and hematopoietic progenitor cell (HPC) proliferation and differentiation stimulated by G-CSF, which impairs HSC self-renewal and may exhaust the BM capacity to exacerbate IR-induced LT-BM injury. Methods C57BL/6 mice were exposed to 4 Gy γ-rays of total body irradiation (TBI) at a dose-rate of 1.08 Gy per minute, and the mice were treated with G-CSF (1 μg/each by ip) or vehicle at 2 and 6 h after TBI on the first day and then twice every day for 6 days. All mice were killed one month after TBI for analysis of peripheral blood cell counts, bone marrow cellularity and long-term HSC (CD34-lineage-sca1+c-kit+) frequency. The colony-forming unit-granulocyte and macrophage (CFU-GM) ability of HPC was measured by colony-forming cell (CFC) assay, and the HSC self-renewal capacity was analyzed by BM transplantation. The levels of ROS production, the expression of phospho-p38 mitogen-activated protein kinase (p-p38) and p16INK4a (p16) mRNA in HSCs were measured by flow cytometry and RT-PCR, respectively. Results The results of our studies show that G-CSF administration mitigated TBI-induced decreases in WBC and the suppression of HPC function (CFU-GM) (p < 0.05), whereas G-CSF exacerbated the suppression of long-term HSC engraftment after transplantation one month after TBI (p < 0.05); The increase in HSC damage was associated with increased ROS production, activation of p38 mitogen-activated protein kinase (p38), induction of senescence in HSCs. Conclusion Our findings suggest that although G-CSF administration can reduce ARS, it can also exacerbate TBI-induced LT-BM injury in part by promoting HSC senescence via the ROS-p38-p16 pathway.